An evidence map of clinical practice guideline recommendations and quality of non-pharmaceutical interventions for post-stroke emotional disorders - Li, Ye; Zhang, Jing; Li, Jia-ji; Zhao, Dan; Tang, Ling; Jin, Ying-Hui (Frontiers in Neurology, 2025)
BackgroundClinical practice guidelines (CPGs) have an indispensable role in guiding the selection of various non-pharmaceutical interventions (NPIs) for post-stroke emotional disorders (PSED). However, little is known about their quality and recommendations. This study aims to critically appraise the quality of existing NPIs for PSED CPGs and extract relevant recommendations, present the research distribution of various NPIs in an evidence map, and assist clinicians in making decisions.MethodsA systematic search was undertaken in PubMed, Embase, CINAHL, Web of Science, China National Knowledge Infrastructure, Wanfang, VIP, SinoMed, and international guideline developing institutions from origin to November 20, 2024, to identify the CPGs on NPIs for PSED. The CPGs finally selected were blindly evaluated by two reviewers using the Appraisal of Guidelines Research & Evaluation (AGREE) II instrument and the reporting quality was evaluated using the RIGHT statement. The overall agreement among reviewers was analyzed using intraclass correlation coefficient (ICC).ResultsNine guidelines were included and evaluated. Two CPGs were grade A (recommended) and seven CPGs were grade B (recommended with modification). The reporting rate of RIGHT ranged from 40.00 to 80.00%. Nine NPIs were extracted, and there were similarities and differences between the recommendations.ConclusionThis study provides specific direction for improving the quality of CPGs for NPIs for PSED, and provides useful information for clinicians and stakeholders, and provides a basis for clinical decision-making.